HUBUNGAN KINERJA PETUGAS DAN TINGKAT KEPUASAN PASIEN POLI UMUM DI PUSKESMAS TANJUNG KARANG - Rahmi Lestari; Lalu Sulaiman; Sismulyanto Sismulyanto (Jurnal Ilmiah Global Education, 2023)
Satisfied patients are a very valuable asset because if patients are satisfied, they will continue to use the services of their choice. Based on data on the number of patient visits to general polyclinics from 2021 there were 11,657 while in 2022 there were 10,013 with an average of 30 patient visits per day. The purpose of this study was to determine the relationship between officer performance and patient satisfaction at the General Polyclinic at the Tanjung Karang Health Center, Mataram City. The research design was "cross-sectional". A sample of 92 people was taken by random sampling method, namely by accidental sampling from a population of 2,625. Data was collected by interview method with a questionnaire tool. Data analysis was performed by Chi-Square analysis. The results of the Chi-Square test show that there is a relationship between officer performance and general polyclinic patient satisfaction with statistical tests that there is a low/weak relationship with a correlation coefficient value of a significant positive direction and a significant test is carried out so there is a relationship between the two variables because the p-value or Sig of 0.00 or less than 0.05 (5%). Suggestions in this study are that there is a need to increase the performance of officers such as responsiveness, providing clear and precise information about the disease, giving attention or understanding to patients so that patients feel safe during examinations and equipment for the physical facilities of the Tanjung Karang Health Center General Polyclinic.